Changes in outpatient antibiotic utilization, 2000–2016: More people are receiving fewer antibiotics. (15th February 2019) - Cocoros, Noelle M.; Ochoa, Aileen; Klompas, Michael
Abstract: We examined annual outpatient antibiotic dispensings within a health insurance plan covering ∼970, 000 members per year during 2000–2016. The proportion of members with antibiotic dispensings decreased from 33.3% in 2000 to 25.9% in 2016. This trend was consistent in all stratifications of age, race/ethnicity, sex, and comorbidities.